Міжнародне співробітництво під час розслідування воєнних кримінальних правопорушень - Чернецька, Олена Василівна; Чернецька, Олена (Державний податковий університет, 2025)
У статті розглянуто особливості міжнародного співробітництва правоохоронних органів під час розслідування воєнних кримінальних правопорушень. Зазначено, що дослідження міжнародної співпраці у розслідуванні воєнних кримінальних правопорушень є надзвичайно актуальним у сучасних умовах, зокрема в контексті ведення повномасштабної війни на території України. Ефективне розслідування таких кримінально-протиправних посягань вимагає тісної взаємодії між державними органами, міжнародними інституціями та громадянським суспільством. Доведено, що співпраця держав у розслідуванні воєнних кримінальних правопорушень є ключовим елементом забезпечення справедливості та покарання винних осіб. Вона охоплює обмін інформацією, створення спільних слідчих груп, екстрадицію підозрюваних та інші форми взаємодії. Завдяки такій співпраці міжнародне співтовариство може ефективно реагувати на серйозні порушення міжнародного права. Зроблено висновок, що створення спільних слідчих груп дає змогу об’єднати ресурси та експертизу різних країн для ефективного розслідування воєнних кримінальних правопорушень. Наприклад, у березні 2022 року Україна, Литва та Польща утворили спільну слідчу групу для розслідування злочинів агресії та воєнних кримінальних правопорушень, вчинених російською федерацією. Пізніше до цієї групи приєдналися Естонія, Латвія та Словаччина. Ця група стала однією з найбільших у історії діяльності Євроюсту. Визначено, що розслідування воєнних кримінальних правопорушень є складним та ресурсозатратним процесом, який вимагає тісної співпраці між державами. Зарубіжні країни надають Україні різноманітну допомогу в цій сфері, охоплюючи правову експертизу, технічну підтримку та участь у спільних слідчих групах.

The article examines the peculiarities of international cooperation of law enforcement agencies in the investigation of war criminal offences. It is noted that the study of international cooperation in the investigation of war criminal offences is extremely relevant in modern conditions, in particular in the context of a full-scale war on the territory of Ukraine. Effective investigation of such criminal offences requires close cooperation between state authorities, international institutions and civil society. It is proved that cooperation of states in the investigation of war crimes is a key element of ensuring justice and punishment of perpetrators. It includes the exchange of information, creation of joint investigative teams, extradition of suspects and other forms of cooperation. Through such cooperation, the international community can effectively respond to serious violations of international law. It is concluded that the creation of joint investigative teams allows combining the resources and expertise of different countries for the effective investigation of war crimes. For example, in March 2022, Ukraine, Lithuania and Poland formed a joint investigation team to investigate crimes of aggression and war crimes committed by the Russian Federation. Later, Estonia, Latvia and Slovakia joined the group. This group became one of the largest in the history of Eurojust. It is determined that the investigation of war crimes is a complex and resource-intensive process that requires close cooperation between states. Foreign countries provide Ukraine with various types of assistance in this area, including legal expertise, technical support and participation in joint investigation teams. The article highlights the main areas of foreign assistance in the investigation of criminal offences: 1. Legal and technical support. International partners, including the European Union, provide Ukraine with legal expertise and technical assistance for the effective investigation of war crimes. This includes staff training, exchange of experience and provision of necessary resources. 2. Financial support. Funding from external assistance, in particular from the United States of America, is essential to provide resources for war crimes investigations. However, the freezing of such funding could have a negative impact on the ability to conduct investigations. 3. Participation in international investigative teams. The creation of joint investigative teams involving representatives of different countries allows for the pooling of resources and expertise for effective investigations. For example, Ukraine, Lithuania and Poland have established a joint investigation team to investigate crimes of aggression and war crimes committed by the Russian Federation. 4. Cooperation with international organisations. Interpol provides Ukraine with access to its tools for investigating war crimes, which facilitates effective information exchange and coordination between law enforcement agencies of different countries.
Keywords: воєнні злочини; розслідування; Міжнародний кримінальний суд; міжнародне співробітництво; кримінальні правопорушення проти миру та безпеки людства; зарубіжний досвід; war crimes; investigation; International Criminal Court; international cooperation; criminal offences against peace and security of mankind; foreign experience